Crack propagation mechanisms of an aged nickel-titanium-hafnium shape memory alloy. (15th January 2019) - Amin-Ahmadi, Behnam; Noebe, Ronald D.; Stebner, Aaron P.
Abstract: Mechanisms of crack propagation in a NiTiHf sample were studied from post-mortem microstructure characterizations about cracks. Transmission electron microscopy (TEM) analysis showed that a crack propagated within a martensite band along 〈011〉 type II twin planes. The crack was observed to switch between different twin planes to avoid precipitates. The crack tip terminated outside of the martensite band, within surrounding austenite. Amorphization of crack edges in both austenite and martensite was also detected, together with Ni enrichment. High-resolution TEM examination of crack tip inside the austenite phase also confirmed the formation of martensite nanocrystals embedded in the amorphous regions. Graphical abstract: Unlabelled Image